Early internationalisation of high-tech firms: past accomplishments and future directions. (2015) - Neubert, Michael
This article provides an evaluative overview of international management literature, in which the current research accomplishments of early and fast internationalisation of high-tech start-up firms from small and open economies using the example of Switzerland are analysed. The author puts a special emphasis on how born-global firms from small and open economies might use traditional internationalisation theories like the Uppsala internationalisation process model to acquire new clients in new foreign markets early and fast after their incorporation. The article discusses convergent and divergent findings in terms of conceptual and empirical issues and set forth areas for future qualitative and quantitative research.